Examining the impact of home purchase restrictions on China's housing market - Zhentong Lu; Sisi Zhang; Jian Hong (Bank of Canada, 2021)
This paper studies the impact of home purchase restrictions on China's housing market. We estimate a structural model of household preference for housing, real estate developers' pricing decisions, and equilibrium market outcome in five large cities. By comparing the estimation results from pre- and post-policy intervention, we find that after home purchase restrictions are implemented, overall housing demand in most cities becomes weaker and less price elastic; meanwhile, real estate developers face higher holding costs and thus are willing to lower prices and sell more quickly. Counterfactual analyses show that in some cities, alternative policy designs that cause less structural change of demand could improve consumer welfare and social welfare better than the implemented policy.
Keywords: R31; R38; O18; 330; Housing; Market structure and pricing